2008
DOI: 10.1017/s096719940800484x
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous hyalin and sea urchin gastrulation. Part III: Biological activity of hyalin isolated fromLytechinus pictusembryos

Abstract: SummaryHyalin is a large glycoprotein, consisting of the hyalin repeat domain and non-repeated regions, and is the major component of the hyaline layer in the early sea urchin embryo of Strongylocentrotus purpuratus. The hyalin repeat domain has been identified in proteins from organisms as diverse as bacteria, sea urchins, worms, flies, mice and humans. While the specific function of hyalin and the hyalin repeat domain is incompletely understood, many studies suggest that it has a functional role in adhesive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…We showed that hyalin is localized on both the archenteron and blastocoel roof (Carroll et al ., 2008). We showed that hyalin and anti-hyalin antibody block the cellular interaction using the microplate assay (Razinia et al ., 2007; Alvarez et al ., 2008; Carroll et al ., 2008; Contreras et al ., 2008) and finally here, using exogenous hyalin, in the direct pieces assay. We propose that exogenously added hyalin binds to the hyalin on the two pieces of the cellular interaction (hyalin is known to selfassociate) and in this way blocks adhesion.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…We showed that hyalin is localized on both the archenteron and blastocoel roof (Carroll et al ., 2008). We showed that hyalin and anti-hyalin antibody block the cellular interaction using the microplate assay (Razinia et al ., 2007; Alvarez et al ., 2008; Carroll et al ., 2008; Contreras et al ., 2008) and finally here, using exogenous hyalin, in the direct pieces assay. We propose that exogenously added hyalin binds to the hyalin on the two pieces of the cellular interaction (hyalin is known to selfassociate) and in this way blocks adhesion.…”
Section: Discussionmentioning
confidence: 96%
“…The pieces assay results indicate that untreated hyalin blocks the adhesion of the archenteron and blastocoel roof, that was previously only suggested using the microplate assay (Razinia et al ., 2007; Alvarez et al ., 2008; Contreras et al ., 2008). In addition, using both the pieces assay and the microplate assay, we show that periodate-treated hyalin did not block the adhesive interaction, while untreated hyalin did.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Majority of reports on cell adhesion in sea urchin embryos were focused on gastrulation and less on blastulation. Several types of aggregation factors, some of which have been isolated and partially characterized [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], as well as more defined proteins such as desmosome cadherins [ 28 , 29 , 30 ], fibronectin [ 23 , 31 , 32 ], laminin [ 32 , 33 ], collagen type I, III and IV [ 34 , 35 , 36 , 37 ], integrin [ 38 ], lectins [ 39 ] including Pi-nectin [ 11 , 38 ] and echinonectin [ 12 , 40 , 41 , 42 , 43 ], hyalin [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], proteoglycans [ 40 , 52 , 53 , 54 , 55 , 56 ], and glyconectin type of glycans [ 15 , 16 ], were shown to promote cell–cell adhesion and cell–extracellular matrix adhesion that were implicated in the maintenance of sea urchin embryonal shape and morphogenesis.…”
Section: Introductionmentioning
confidence: 99%